IMPLEMENTASI MEDIA MISTERI BERGAMBAR DALAM PEMBELAJARAN INFLASI UNTUK MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR - Pancasari, Devi; Aini, Karina Nur; Indarti, Nunuk (Jurnal Edukasi Ekonomi, 2025)
The quality of learning has a significant impact on educational success. In the economics subject, inflation teaches why the prices of consumed goods are increasing. This research aims to improve the learning outcomes of class XI students in inflation material by developing mystery picture media in high schools. This research uses a type of classroom action research (PTK) by applying a research design from Kemmis & Taggart which includes four stages: planning, action, observation, and reflection. The research subjects were 36 class XI students at SMAN 1 Taruna Madani East Java. Data collection techniques involve learning results tests, observation, and documentation. Data analysis was carried out descriptively qualitatively and quantitatively, with success indicators determined for more than 80% of students who exceeded the KKM. The results of the research show that the application of the development of pictorial mystery learning media in the Economics subject with inflation material has succeeded in improving student learning outcomes. Before the action, only 26 students or 72.2% exceeded the KKM. In cycle I, the number of students who exceeded the KKM was 77.8%, with an increase in the class average score from 82.3 to 84.8. In cycle II, 34 students or 93.8% exceeded the KKM, with the class average score increasing from 84.8 to 93.8. In conclusion, pictorial mystery learning media has proven to be effective in improving student learning outcomes, and overall, this research makes a positive contribution to increasing student academic achievement.